Effects of Added 25(OH)D3 With Varying Standardized Total Tract Digestibility of Phosphorus Levels on Nursery Pig Performance, Bone and Urine Characteristics, and Serum Vitamin D - Larissa L. Becker; Jordan T. Gebhardt; Mike D. Tokach; Robert D. Goodband; Joel M. DeRouchey; Jason C. Woodworth; Jon R. Bergstrom (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 360 pigs (DNA 600 × 241; initially 12.8 ± 1.18 lb) were used in a 45-d growth study to evaluate the effects of added 25(OH)D3 with three levels of STTD P on nursery pig growth performance, bone and urine characteristics, and serum vitamin D. Pigs were weaned at approximately 19 d of age and randomly allotted to one of six dietary treatments. A total of 72 pens were used with five pigs per pen and 12 replications per treatment. Dietary treatments were arranged in a 2 × 3 factorial with main effects of 25(OH)D3 (0 or 50 μg/kg estimated to provide an additional 2,000 IU/kg of vitamin D3; Hy-D, dsm-firmenich, Plainsboro, NJ) and STTD P (70, 100, or 130% of the NRC requirement estimate on a dietary percentage basis). All diets contained 1,653 IU/kg of vitamin D3 provided by the vitamin premix, but the premixes did not contain additional 25(OH)D3. Diets were corn-soybean meal-based and fed in three phases. On d 45, one pig per pen was euthanized to collect the right fibula, metacarpal, and second and tenth ribs. Overall, increasing STTD P increased (quadratic, P < 0.003) BW, ADG, ADFI, and improved F/G with minimal improvement above 100% of the NRC STTD P requirement. Added 25(OH)D3 had no effect (P > 0.10) on growth performance. Pigs fed increasing STTD P had decreased urinary Ca concentration (linear, P < 0.001 and quadratic, P = 0.078) and increased urinary P concentration (quadratic, P < 0.001), with all pigs fed 70% of the NRC STTD P requirement having non-detectable levels of P in the urine. Added 25(OH)D3 had no effect (P > 0.10) on urine Ca and P concentrations. A quadratic 25(OH)D3 × STTD P interaction (P = 0.032) was observed for serum 25(OH)D3. When pigs were fed added 25(OH)D3, serum 25(OH)D3 increased (quadratic, P = 0.005) as STTD P increased but no differences (P > 0.10) were observed when no 25(OH)D3 was added and STTD P increased. A quadratic STTD P × 25(OH)D3 interaction was observed for 1,25(OH)2D3 concentrations (P = 0.002). When pigs were fed added 25(OH)D3, serum 1,25(OH)2D3 decreased (quadratic, P < 0.001) as STTD P increased. When no 25(OH)D3 was included, no differences were observed (P > 0.10). No STTD P × 25(OH)D3 interaction was observed for 24,25(OH)2D3. Pigs fed diets with added 25(OH)D3 had increased (P < 0.001) serum 24,25(OH)2D3 concentration. Added 25(OH)D3 had no effect (P > 0.10) on serum 1,25(OH)2D3 but concentrations decreased (quadratic, P = 0.001) as STTD P increased. Bone density of metacarpals increased (linear, P = 0.001) as STTD P increased, as did the fibulas and ribs (quadratic, P ≤ 0.055). The percentage bone ash and bone ash weight increased (quadratic, P ≤ 0.065) for all bones as STTD P increased. Added 25(OH)D3 had no effect on bone density or bone ash weight for any of the bones (P > 0.10); however, the reduction in bone ash observed with reducing STTD P level tended to be less when 25(OH)D3 was provided (linear interaction, P = 0.098). In summary, added 25(OH)D3 had limited effect on growth performance, urine Ca and P, or bone characteristics; however, added 25(OH)D3 increased serum concentrations of 25(OH)D3 and 24,25(OH)2D3. Increasing STTD P to 100% of NRC (2012) requirement estimate increased growth and 130% of NRC maximized bone ash.
Keywords: vitamin D; nursery pig; bone